Examining the Flocs Rise Velocity of Electrocoagulation with Intensified Microbubbles - Tarmizi Tasnim; Niza Noorzalila Muhammad; Razak Norizham Abdul (E3S Web of Conferences)
The rising pollution from household and industrial waste has exacerbated the leachate issue, necessitating effective treatment methods like electrocoagulation (EC). The role of vibrated electrode plates (VEPs) is to enhance floc formation during EC that improve the interaction between pollutant particles and coagulant ions, leading to better floc formation. Flocs’ hydrodynamic performance can be evaluated by determining the mean rise velocity (RV) during the process. In the present study, the RV of flocs under different current intensity (CI) levels during EC employing VEPs and stationary electrode plates (SEPs) was investigated using particle image velocimetry (PIV). The results showed that, at CI=4.5A, the flocs’ RV during EC with VEPs was 12.77 mm/s compared to 8.65 mm/s with SEPs. Moreover, flocs had higher RV when CI was higher (4.5A); it varied from 0.74 mm/s at 0.5A to 8.65 mm/s during EC with SEPs. The changes in RV closely correlate with the introduction of an agitation mechanism that improves the ionic transfer between particles and bubbles in the wastewater solution.